Post War Theological Underpinnings of the Youngsters of the District of Jaffna and the Prolonged Violence - Judethas, T. (University of jaffna, 2024)
The Tamils of Sri Lanka were forced to opt for violent means to safeguard their basic and innate human rights. The visible outcome of the internal groaning is the armed struggle for more than three decades. The pathetic state of this reality is that the real yearnings of the Tamils are still not yet met properly. Youngsters who are the war children, belonging to the District of Jaffna have become a prey to the ancestral groaning for freedom. This paves way for many disorders at present. The aspect of violence within their hearts bubbles up at times to unmannerly behaviours. The death rate accelerates very high because of gang fights, accidents, drug consumption, suicide, etc. The main purpose of this paper is to dealing with the thread line of violence that permeates the minds of the youngsters; it will elaborate on the present and violent behavioural pattern of the youngsters. It will be elucidating the sponsors, the collaborators and of the people who are behind the scene. The causes for this problem must be identified and eliminated. Synchronic and diachronic methods will be employed. Data are to be collected using deductive method. The results of the paper would be identifying and solving the root causes of the Tamils’ struggle that hinder the good future of our beautiful country. Our youngsters are the valuable future leaders; therefore, they should be guided properly. The sitz in leben of Jesus’ earthly life corresponds to our era. Jesus incorporated a variety of youngsters into his college of disciples. The conclusion would be, unless we accommodate a reconciliatory theology we may lose many of our youngsters very shortly.
Keywords: Sitz in leben; Reconciliatory theology; Thread line; Root causes; Groaning